Les cadres quasi-indépendants : du contrat de travail au contrat d’activité dépendante - Alibert, Anne-Claire (Université Clermont-Ferrand 1, 2005)
A défaut de définition légale du cadre, la notion est fonctionnelle et s’applique à des modes de fonctionnement, allant du salariat traditionnel au quasi-entrepeneuriat. Aujourd’hui, les cadres exerçant un pouvoir de commandement s’effacent devant les cadres experts mettant en oeuvre une compétence technique. Leur mode de fonctionnement professionnel est de moins en moins en adéquation avec le droit du travail : le contrat de travail classique devient incongru pour le cadre quasi – indépendant qui dispose d’autonomie, s’affranchit du lien de subordination et participe au pouvoir de direction. Face à l’inadaptation du droit et à son impuissance, il est nécessaire de construire un régime juridique pour ces « cadres quasi-indépendants », hors du droit du travail. Malgré un expansionnisme manifeste du droit du travail, se dessine une cohabitation entre salariat et non salariat. L’instauration d’un droit de l’activité, susceptible de regrouper un corps de règles d’application générale, dépassant le clivage traditionnel entre activités salariées et non salariées peut apporter des éléments de réponse aux « cadres quasi-indépendants », désireux de sortir de la protection traditionnelle inadaptée du droit du travail. Aussi plutôt que de « forcer » le cadre traditionnel du droit du travail en multipliant les exceptions et statuts dérogatoires pour protéger des pseudos salariés, il semble préférable de faciliter le passage du contrat de travail au contrat d’entreprise, en l’aménageant en cas de « dépendance économique » pour en faire un contrat d’activité sécurisé (cf parasubordination)
Keywords: Cadres (personnel); Contrat de travail; Droit du travail; France; Labour law

The role of implicit contract terms as a determinant of contractual consequences - Bailly, Chantal (Stellenbosch University, 2005)
Banks are one of the most important elements in the economic cycle of modem society. As money replaced bartering banks have gradually moved into the pivotal point of the relations between participants in the economic cycle. No project can be realized without money today. On the one hand, there are the investors who, irrespective of the amount, entrust their assets to the banks. On the other hand, there are those whose financial needs require the granting of some form of credit. Banks operating in these contexts clearly bear important responsibilities towards the different parties. A third party, the state, is also interested in a well-functioning banking establishment. Economic stability, without which there can be no political stability, cannot otherwise be ensured. The state is accordingly keenly interested in maintaining the operability of this system. To this end, various laws are made in the respective countries aimed at supervising the banking industry. This work deals with some of the legislation relating to bank supervision in the Federal Republic of Germany and the Republic of South Africa. In the various chapters certain aspects of bank supervision in the two countries are identified, juxtaposed and compared. The reasons for any differences are sought, discussed and where possible explained. From a historical point of view, the two countries developed differently. Nevertheless, the need to regulate this sector through legislative means arose at an early stage in both. Unfortunately, the catalyst for legislative development was mostly some or other financial crisis. Any measures for supervising banks must, to be binding, be constitutional. In this regard much must still be done in South Africa due to the fact that the New Constitution has only been in force since 1996. Thus certain regulations stemming from the Banks Act 90 of 1994 need to be reconsidered in the light of the constitution. Bank supervisory activity is performed by a national institution in both countries. Germany avails itself of an independent authority. However, in South Africa it is one of the tasks of the central bank which has established a specific office for this purpose. Legal and natural persons alike are subject to such supervision. Diverse other government institutions provide support for such supervisory work in both countries. The scope of banking supervision, that is the persons and transactions affected, is broad and also finely meshed. Both systems list a number of banking transactions that are subject to their supervision. This affects all domestic banks and all foreign banks that are domestically active. Access to the banking business is only permitted in both countries after an appropriate license has been granted. The license can be conditional. Moreover, both systems make provision for the revocation of the license in appropriate circumstances. The conducting of banking business without the necessary permission is forbidden in both countries under the threat of legal punishment. It is well recognized in modem society that legal subjects should be protected against the decisions of those who wield state power. The possible remedies of those affected by the decisions of the public authorities responsible for banking supervision in the different countries are investigated in conclusion.
Keywords: Contracts; Good faith

The legal regulation of corporate governance with reference to international trends - Horn, Roelof Combrinck (University of Stellenbosch, 2005)
Corporate governance is defined as the system by which companies are managed and controlled. The concept came to the fore with the Cadbury Report in England in 1992 and has since been the topic of much academic discussion. The recent collapse of companies like Enron and WorldCom raised serious questions about international corporate governance practices. This has resulted in widespread reform. In the United States large-scale prescriptive measures were implemented through the enactment of the Sarbanes-Oxley Act. The United Kingdom persisted with their principle-based approach of comply or explain, although some amendments were made to the Combined Code through a joint effort by the Co-ordinating Group on Audit and Accounting Issues, the Smith Report and the Higgs Report. In Australia change took the form of the ASX Corporate Governance Principles and CLERP 9. South Africa, influenced by its common law background, followed a similar approach to that of the United Kingdom but has recently adopted a more prescriptive approach similar to that of the US. The King Committee was set up to review corporate governance in South Africa and two reports report were published – one in 1994 and another in 2002. Amendments to the JSE Listings Requirements followed. The Konar Report made recommendations on the reform of the accounting and auditing profession. The Department of Trade and Industry has recently launched a review of South African company law in conjunction with a review of the audit and accounting professions. These recent developments in company law will however not be discussed in depth as it is at a very early stage and is still subject to change. The aim of this study is to evaluate and determine whether or not the reform in South Africa is adequate to address the questions raised by recent corporate scandals in South Africa. The question also has to be asked whether South Africa should follow international trends in reform just for the sake of reforming. This requires an understanding of the principles underlying corporate governance and the reasons for the existence of corporate governance rules. With the increasing separation between ownership and control the accountability of directors has waned considerably. When addressing corporate governance issues, this must be kept in mind constantly. While the focus of recent reform has been on the company, its directors and auditors, the role of shareholders should not be ignored. What is needed to prevent directors and managers from abusing their positions of power are more informed and involved shareholders. The different role players must also cooperate in developing a culture of ethical behaviour and an environment of openness and accountability.

A comparative legal study of the dilution of registered trade marks in selected jurisdictions to further the development of the remedy in South African law - Van der Walt, Elizabeth Margaretha (Stellenbosch University, 2005)
Trade marks are among the most valuable commodities of the modern business world. Adequate protection for trade marks to prevent the misappropriation of their incredible marketing power is therefore important. The aim of this dissertation is to make recommendations regarding the further development of existing South African law regarding the protection of registered trade marks against dilution, particularly by the courts. Current statutory protection is examined and compared with trade-mark law in the United States and the European Union. Although the concept of dilution originated in Germany, most of its development took place in the United States, starting in 1927 with an article by Frank Schechter. Dilution occurs when the awareness that a specific mark signifies a single product from a single source changes to an unmistakable awareness that the same mark signifies various things from various sources. The primary theories as to how dilution occurs are blurring and tarnishment. Although the dilution concept is widely recognised, there is still a debate amongst legal scholars on whether trade marks deserve protection against dilution. The extent of protection that the law gives to trade marks largely depends on the socioeconomic functions that a trade mark is perceived to fulfil. The original source or origin function is protected by the traditional infringement provisions. The identification or distinguishing function, quality function and advertising function subsequently gained recognition. The advertising function is statutorily recognised in various jurisdictions, which prevents trade-mark dilution. Statutory recognition of dilution in the United States first occurred in State law from 1947 onwards. Protection is generally given to distinctive or strong trade marks where a similar mark is used on dissimilar goods in the absence of confusion in such a way that there is a likelihood that the reputation of the senior mark will be injured. The parameters of the concept were developed and refined mainly through case law. Federal protection against dilution was only introduced in 1995. The new Act, although widely welcomed, also brought some unpredictability and interpretation problems. The first statutory dilution protection for trade marks in Europe is found in the Uniform Benelux Trade Marks Act. In 1989 the European Union adopted the Trademark Directive, with the aim of harmonising the legal protection afforded to trade marks. Its "dilution" provisions were incorporated into the United Kingdom's Trade Marks Act of 1994. The sometimes conflicting interpretations of these provisions by the English courts and the Court of Justice of the European Communities are discussed. The South African Act shows a substantial degree of harmony with legislation in the United Kingdom and other European countries. Aspects of the wording of the dilution provisions are however open to interpretation by the courts. Until the end of 2003 there was only one major trade-mark dilution case decided by a South African court, namely SAR v Laugh It OjJPromotions, which is discussed in detail. The dissertation concludes with recommendations to aid South African courts in the future interpretation and application of the dilution provisions. Amendments to the legislation are also proposed to promote greater clarity.
URI: http://hdl.handle.net/10019.1/50239
Keywords: Brand name products; Comparative law; European Union countries; Intellectual property; South Africa; Trademarks; United States

La décomposition du droit de propriété sous l'effet du contrat - Eeckhoudt, Marjorie (Université Lille 2, 2005)
Notre conception de la propriété oscille, depuis l’Antiquité, entre une propriété unifiée et une propriété divisée. Le Code civil a opté pour la première solution. Pourtant, dans le même temps, il a admis l’existence des démembrements de la propriété et accordé aux parties une liberté contractuelle. On pouvait donc penser que, dès 1804, le ver était dans le fruit et qu’il suffisait de repousser les frontières de la liberté contractuelle pour faire ressurgir les propriétés simultanées. Mais, la doctrine a défendu l’unité du droit en limitant le nombre des droits réels puis en contestant la notion de démembrement. Pourtant, le démembrement de la propriété est une technique largement consacrée en droit positif. Quant au numerus clausus des droits réels, il n’y a aucune raison de le soutenir. En exploitant les silences permissifs du droit, il est possible de créer de nouveaux démembrements de la propriété. Sous l’effet du contrat est réapparue l’idée d’un dédoublement du droit de propriété.
Keywords: Démembrement de propriété; Fiducie; France; Propriété immobilière; Usufruit

Le sort des contrats dans les opérations de fusion et de scission de sociétés commerciales - Albortchire, Adamou (Université d'Auvergne - Clermont-Ferrand 1, 2005)
Les Contrats sont des outils omniprésents dans la vie de l'entreprise commerciale et conditionnent, dans une large mesure, son activité économique. Or, plusieurs évènements peuvent, au cours de son existence, affecter son évolution parmi lesquels on peut noter les fusions et scissions. Dès cet instant, deux questions peuvent se poser en ce qui concerne le sort aprticulier des contrats à son actif. Ceux-ci sont-ils supposés se poursuivre en dépit de la disparition de la personne morale contractante ? Ou, au contraire, sont-ils voués à disparaitre au même titre qu'elle ? En d'autres termes, ces opérations sont-elles constitutives de causes de caducité principielle du contrat ? Dans le cas ou ces contrats seraient destinés à poursuivre, le sont-ils tous ? La loi du 5 janvier 1988 qui a réformé et modernisé le régime juridique des fusions et scissions ainsi que la jurisprudence nous ont donné des réponses. Il est, de façon générale, admis que les opérations susvisées se caractérisent par le fait qu'elles impliquent la transmission universelle du patrimoine de la société qui disparaît au profit de la ou des sociétés bénéficiaires. Le principe de poursuite de l'activité contractuelle étant général et automatique, puisque la transmission est "universelle", il s'applique, par cons"quent, à tous les contrats en cours, quels qu'ils soient, de l'entreprise contractante dissoute sans liquidation. Cependant, ce principe, fût-il général, ne se révèle pas pour autant absolu. C'est à dire qu'il comporte malgrès tout des limites. C'est le cas, par exemple, lorsque soit une disposition légale spécifiques, soit une clause de non transmission adéquate empêchent la poursuite automatique du contrat.
Keywords: Contrats; Droit des sociétés commerciales; France; Fusion d'entreprises

Essai sur le contrat de service en droit international privé - Cavalier, Georges A. (Université Jean Moulin Lyon 3, 2005)
Dans l'Union européenne, la notion de contrat de services a pris place au cœur du règlement des conflits de juridictions, et oriente la réflexion en matière de conflit de lois. Elle est en passe de devenir une catégorie du droit international privé, dans l'un des domaines en apparence épuisé et pourtant fondamental de cette discipline : celui du contrat. Cette évolution, confirmée par la récente proposition dite " directive Bolkestein ", ouvre des perspectives nouvelles et soulève toute une série de questions inédites, étudiées à la lumière des droits communautaire, français et néerlandais. C'est donc à l'analyse de cette notion en construction du contrat de services que la première partie de la thèse est consacrée. L'étude défend l'idée qu'en droit français, la définition de l'internationalité des services pose problème, car il n'est pas aussi facile d'identifier un passage de services au travers de la frontière qu'un mouvement de biens. Le droit communautaire recourt à une notion plutôt large : déplacement de l'une des deux parties au contrat et pas seulement des services transfrontaliers. Il semble mieux appréhender leur internationalité. La notion de contrat de services demeure donc autonome en droit international privé, y compris par rapport au – ou au sein même du – droit communautaire, puisqu'elle dépend du texte à interpréter. Les conventions de droit international privé attestent de l'affinité qu'entretient le contrat ayant pour objet des services portant sur un meuble, avec la qualification de vente. Au contraire, les contrats ayant pour objet des services portant sur un immeuble ressortiraient pleinement de la qualification de services. De cette notion en construction procède un régime du contrat de services en voie d'unification, objet de la deuxième partie de la thèse qui prend également quelques distances avec le droit positif. L'influence grandissante de la libre prestation de services communautaire, et ceci plus encore si la directive Bolkestein venait à être adoptée, pourrait bien élever la présomption de la " loi du prestataire " au rang de véritable principe : celui du pays d'origine. En définitive, la loi du prestataire ne se verrait court-circuitée que par l'autonomie de la volonté ou par les lois de police, notamment communautaires, auxquelles se cantonnent les mécanismes d'éviction. Quant au juge compétent, le Règlement Bruxelles I opère une simplification allant dans le sens de l'unification soutenue jusqu'alors, puisqu'il aide à l'interprétation des textes internes ou influence les législateurs nationaux. En effet, outre le juge du domicile du défendeur, le juge alternativement compétent est celui du lieu de livraison de la chose, objet des services, ou – si les services sont immatériels – celui du lieu de leur fourniture.
Keywords: Contrats; Contrats internationaux; Droit international privé; Droit international économique; Services

L'Etat et les risques des entreprises - Dubreuil, Charles-André (Université Paris 2, 2005)
Les entreprises sont soumises à des risques qui dépassent les aléas inhérents aux activités économiques. Ils sont anormaux, exceptionnels et déjouent les prévisions raisonnables des entrepreneurs. Ils peuvent être d'ordre sanitaire (ESB, Pneumopathie), naturel (inondations, tempêtes), technologique (pollutions, explosions), économique (choc pétrolier, concurrence déloyale) ou humain (terrorisme, infractions). Certains d'entre eux sont caractérisés par une forte incertitude et constituent des menaces potentiellement catastrophiques pour ceux qui y sont soumis. Répondant à une demande croissante d'intervention provenant des opérateurs, les pouvoirs publics prennent en charge de tels risques et tentent de les prévenir, de les prévoir, de les faire cesser et de réparer leurs conséquences dommageables. Ce faisant, ils tiennent nécessairement compte de la spécificité de la situation de chaque entreprise en adaptant les outils classiques que leur offre le droit public et en adoptant divers outils spécifiques issus de l'analyse économique. Cette prise en charge, apparemment paradoxale dans un contexte d'économie libérale, demeure toutefois soumise à un certain nombre de contraintes dont la liberté d'entreprendre constitue la principale illustration. Elle suppose en effet que l'intervention publique ne vise pas à remplacer l'entrepreneur dans la gestion de son activité, mais se limite à combler ses lacunes et à répondre aux seuls besoins exprimés. Cette subsidiarité tend aujourd'hui à être battue en brèche par une tendance contemporaine visant à exiger de l'Etat qu'il prenne en charge intégralement, en amont comme en aval, l'ensemble des risques subis. L'accueil favorable qui semble être accordé à cette demande invite à s'interroger sur les relations qu'entretiennent désormais les pouvoirs publics et les entreprises et à repenser l'opposition entre interventionnisme économique et libéralisme.
Keywords: Droit public économique; Employeurs; France; Gestion du risque; Responsabilité; Subventions; Économie politique et politique; État

La participation des collectivités territoriales au capital de sociétés - Peltier, Marc (Université Paris 1, 2005)
La législation française se fonde traditionnellement sur un conflit entre l'intérêt général, le but lucratif et le risque d'entreprise. La participation des collectivités territoriales au capital de sociétés est alors en principe interdite. De nombreux textes autorisent cependant des collectivités territoriales à participer au capital de sociétés spécifiques. La protection de l'intérêt général et l'accueil des collectivités territoriales se font dans des groupements qui dérogent au droit commun des sociétés. Ces régimes sont porteurs de risques tant pour la société elle-même que pour les collectivités territoriales. Une autre approche de la participation des collectivités territoriales au capital de sociétés devrait être envisagée. Le droit communautaire pourrait servir de référence en s'inspirant du critère de l'investisseur privé en économie de marché. La transposition en droit interne de ce critère permettrait de faire évoluer le régime de ces sociétés vers le droit commun.
Keywords: Administration locale; Capital social; Droit commercial; France; Investissements de capitaux; Sociétés d'économie mixte

La formation du contrat à distance par voie électronique - Shandi, Yousef (Université Strasbourg 3, 2005)
Le législateur constate que le développement des échanges économiques à distance, surtout sur Internet, repose sur la confiance. Il intervient alors à plusieurs reprises pour lever les obstacles juridiques qui empêchent la conclusion de contrats à distance par voie électronique. Cependant, les dispositions adoptées sont complexes et parfois même critiquables du fait de l'incohérence des différents textes. Ces dispositions portent tout particulièrement sur le processus de la formation de contrat par voie électronique (surtout en ce qui concerne le contenu de l'offre, l'acceptation et la commande) et à la protection du consommateur. Le législateur s'intéresse également au problème de conflit de lois en matière de commerce électronique alors qu'il garde le silence sur les questions de conflit de juridictions et de règlements extrajudiciaires des litiges. The legislator notices that the development of the remote economical exchanges, particularly via the internet is based on confidence. He intervenes on several occasions in order to remove the legal obstacles which stopped the conclusion of remote parties contracts via electronic channels. However the adopted terms are complex and sometimes open to criticism as to the inconsistency of the various texts. Those terms relate especially to the process of formation of contracts via electronic channels (particularly with regard to the content of the offer, the acceptance and the order) and the consumer protection. The legislator takes also interest in the conflict of the laws relating to the e-commerce whereas he remains silent on the subject of conflicts of jurisdictions and the extra-judicial settlements of lawsuits.
Keywords: Achat en ligne; Achats sur Internet; Conflit de juridictions; Consommateur (protection); Offre et acceptation

Essai sur la notion d'économie du contrat - Arsac Ribeyrolles, Audrey (Université d'Auvergne Clermont-Ferrand 1, 2005)
L'Apparition récente du concept d'économie du contrat en jurisprudence permet de mettre au jour ses deux fonctions. D'une part, elle constitue une grille de lecture du contrat. Elle est en effet apparue comme une référence dans la détermination de la loi du contrat, qu'il s'agisse de son contenu obligatoire ou de son régime. Entre objectivisme et subjectivisme, la référence à l'économie du contrat marque une rationalisation de la volonté des parties. A leur intention réelle est substituée une intention normale telle qu'elle émanerait de contractants rationnels. En ce sens, l'économie du contrat est un parangon contractuel, dont la coloration économique est nette et apparaît également une référence pour en apprécier le sort, permettant la survie des contrats utiles et la disparition ou l'adaptation de ceux ne présentant pas ou plus d'intérêt. Une telle fonction n'est cependant admissible qu'à la condition de circonscrire plus étroitement la notion d'utilité. Au-delà de l'intérêt du contrat ou des parties, c'est finalement l'intérêt de l'opération contractuelle que tend à garantir la référence à l'économie du contrat
Keywords: Contrats; France; Obligations (droit)

La responsabilità internazionale dello stato per violazione delle norme OMC : regime speciale o ordinamento particolare? - Bettin, Valentina (European University Institute, 2005)
Defence date: 31 January 2005
Keywords: Government liability; International Law; International Trade; OMC; Organizzazione mondiale del commercio; WTO

L'impact juridique des nouvelles dispositions de la Loi sur les normes du travail en matière de harcèlement psychologique sur le régime légal préexistant - Bourgault, Julie (Université Laval, 2005)
Ce mémoire cherche à déterminer l’impact juridique de l’adoption des nouvelles dispositions en matière de harcèlement psychologique au travail dans la Loi sur les normes du travail, sur le régime légal préexistant concernant le harcèlement au travail. En effet, la généralité des termes de la définition utilisée englobe un grand nombre de situations déjà couvertes par d’autres recours. L’étude des dispositions législatives des différents régimes, ainsi que de la jurisprudence sur le harcèlement en milieu de travail permet de constater que les recours préexistants conservent une utilité pour les victimes. Toutefois, le choix du recours doit tenir compte des différents modèles de compétence, qui varient selon les dispositions et la nature du litige, dans son contexte factuel.
Keywords: Harcèlement (travail); Harcèlement psychologique; Normes du travail

La participation des personnes privées au règlement des différends internationaux économiques : le cas de l'élargissement du droit de porter plainte à l'Organisation mondiale du commerce - Côté, Charles-Emmanuel (McGill University, 2005)
This dissertation explores the legal issues raised by the participation of private persons in the settlement of international economic disputes, using the potential enlargement of legal standing in the World Trade Organisation (WTO) as a case study. In the first part, a typology of the special regime of responsibility of WTO Members is drawn, to serve as a "normative bridge" between the twin phenomenon of legalisation of international trade relations and judicialisation of international trade dispute settlement. In the second part, a comparative study of the participation of private persons in the settlement of international economic disputes is conducted, using the doctrine of diplomatic protection from general international law as the analytical framework. This permits an inventory of the various means of private participation in the current practice of States, as well as shedding light on the main systemic problems that are raised, notably in the field of foreign direct investment, where important developments have taken place. In the third part, a study de lege feranda on the enlargement of legal standing in the WTO dispute settlement mechanism is undertaken. The study is rooted in the previous analysis of the special regime of responsibility of WTO Members and the comparative survey on the participation of private parties in the settlement of international economic disputes. The dissertation demonstrates that the problems concerning private persons in the current mechanism should not be answered by offering them direct access to the WTO, but rather by refocusing attention on the central role of the State in the mediation of diverging interests in the governance of the world trading system. It proposes as a conclusion that WTO Members should instead look into formalising the process of handling private complaints at the domestic level.
https://escholarship.mcgill.ca/concern/theses/q811kp87f
Keywords: Dispute resolution (Law); Foreign trade regulation; OMC; Public-private sector cooperation; WTO; World Trade Organization

Les droits du débiteur en redressement judiciaire - Hardy, Christophe (Université de Reims Champagne-Ardenne, 2005)
À l'occasion des procédures collectives, les droits du débiteur apparaissent sacrifier sur l'autel des intérêts des salariés, de l'entreprise et des créanciers. Le redressement judiciaire n'échappe pas à cette appréciation, qui se révèle toutefois erronées. Le débiteur, loin d'être considéré comme un périèque, constitue le personnage-clé de cette procédure et ses droits sont, en définitive, voisins de ceux d'une personne in bonis. En effet, la désignation d'un administrateur judiciaire, rare en régime simplifié, et davantage axée sur la surveillance et l'assistance en régime générale, ne le place plus dans la position d'un étranger à son redressement. Dans le cadre de son activité professionnelle la réalisation de certains actes, bien que conditionnée par une autorisation judiciaire préalable, ne réduit pas ses droits à néant. L'expression de ceux-ci se traduit, pour l'essentiel, à travers la mise en oeuvre des voies de recours et de la possibilité qu'il a d'exercer une nouvelle activité. Dans le cadre de sa vie privée, l'accomplissement de ses droits personnels demeure de sa compétence exclusive. Toutefois les conséquences patrimoniales de ces derniers intéressent les mandataires judiciaires, qui cependant, n'interviennent pas à l'occasion du débat purement personnel. Les mécanismes juridiques, issus du droit civil et du droit commercial, assurent davantage le renforcement de la sauvegarde de ses droits. Ainsi, le débiteur en redressement judiciaire se situe dans une perspective proche de celle de son homologue in bonis.
Keywords: Créancier; Débiteur; Redressement judiciaire; Voies de recours

Evaluation du fonctionnement et des mandats de la bibliothèque de l'institut international des assurances (I.I.A) Yaoundé-Cameroun - Ndjemga, Roger (Institut International des Assurances (IIA), 2005)

The cultural industries as a regulatory challenge for international trade law : insights from the NAFTA, the WTO and the EU - Neuwirth, Rostam Josef (European University Institute, 2005)
In the universal history of mankind, the concepts “culture” and “trade” have long denominated two important trains of human aspirations and activities. Notwithstanding their great significance for human life in its entirety, they have been widely regarded as belonging to distinct spheres, which were deemed to be difficult, if not impossible, to reconcile. This perception was also widely reflected in the sphere of law, where their respective fields have been subject to separate regimes based on the logic of their mutual exclusivity and expressed in the concept of res extra commercium. By contrast, the concept of “cultural industries”, which was originally derived from the term Kulturindustrie coined by protagonists of the Frankfurt School introduced a new category of cultural goods and services, which began to strongly challenge the traditional legal separation of cultural from economic considerations. Their novelty as well as their more subtle conceptual implications led to the controversy over the treatment of the dual, i.e. both cultural and economic, nature of such goods and services, which surfaced first during the bilateral trade negotiations between Canada and the United States and soon afterwards during the multilateral Uruguay Round negotiations. In the latter, it was the controversy over the exception culturelle that almost derailed the successful establishment of the World Trade Organization (WTO). Since then the problem remains unsolved, and reinforced by the decision of the WTO Panel in the Canada Periodicals Case, the quest for an appropriate conceptual approach allowing for the correct legal answer to the conundrum of culture and trade continues up to this day. In this quest, the present thesis forms an attempt to cast some light on the culture and trade conundrum with a view to isolating options for an appropriate legal response of the multilateral trading system under the WTO. It follows the evolution of the concept of cultural industries, from its birth in the context of critical social theory across the field of political economy to its first appearance in the legal context with the 1988 Canada-United States Free Trade Agreement. After a short analysis of the cultural industries exemption in the North American context, its focus shifts to the GATT/WTO system of which the basic provisions are discussed in connection with the category of cultural goods and services known as the cultural industries. Their critical analysis yields the present imperfections inherent in the WTO system as a corollary of the fragmentation of the international legal order. Before some final conclusions are drawn, these imperfections are contrasted with the relevant experiences within the context of the process of European integration from the European Economic Community to the European Union.
Artwork Medium: Paper Interview Medium: Paper
Keywords: Cultural property; Foreign trade regulation; Property protection